The Role of the Village Consultative Body in Monitoring Villages to Ensure Compliance with Regulations and Promoting Accountability, Transparency, and Budget Discipline in Village Financial Management in the Bengkalis District - Nurul Mawaddah; Husnul Muttaqin (Universitas KH. Abdul Chalim Mojokerto, 2025)
Village financial management requires compliance with regulations and the application of good governance principles, particularly accountability, transparency, and budget discipline. This study aims to analyze the role of the Village Consultative Body (BPD) in overseeing village compliance with regulations and promoting accountability, transparency, and budget discipline in village financial management in Bengkalis District. The study used a qualitative approach with a case study method in 11 villages. Data were collected through interviews with members of the Village Consultative Body (BPD) and village officials as well as documentation studies, then analyzed using qualitative descriptive methods. The results of the study show that the BPD performs a supervisory function at the planning, implementation, and accountability stages of village finances through communication and coordination with the village government. However, the effectiveness of supervision still faces limitations in terms of administrative authority, supporting facilities, and the time available to BPD members. These findings emphasize the need to strengthen capacity and institutional synergy in order to improve the quality of village financial management.